Impact of ethanedinitrile rates and application method on nutsedge species and tomato root galling. (February 2019) - Stevens, Mary C.; Freeman, Joshua H.; Boyd, Nathan S.
Abstract: The pre-plant soil fumigant ethanedinitrile (EDN) has shown promising activity against several key pests including plant-parasitic nematodes, a variety of weeds, and soil-borne pathogens. With chemical properties similar to those of methyl bromide, EDN has the potential to move readily through the soil profile. EDN is being investigated as a pre-plant soil fumigant alternative to current industry standards for Florida plasticulture vegetable production. EDN was applied via shank injection, vapor, and drip irrigation. Control of nutsedge species and plant-parasitic nematode species was determined and compared to a non-treated control and a mixture of 39% 1, 3-dichloropropene and 59.6% chloropicrin (1, 3-D:Pic) in tomato and watermelon. In these studies, EDN performed as well as 1, 3-D:Pic and significantly better than the nontreated control against nutsedge species. EDN applied as a vapor resulted in significantly increased nematode incidence at one location when compared with most other treatments. Highlights: EDN controlled nutsedge species as well as 1, 3-D:Pic. EDN applied as a vapor did not control nematodes as well as EDN applied via shank. Results indicate EDN has potential to be used as a soil fumigant.